2019
DOI: 10.1057/s41599-019-0223-z
|View full text |Cite
|
Sign up to set email alerts
|

Teaching digital fiction: integrating experimental writing and current technologies

Abstract: Today's creative writers are immersed in a multiplicative, multimodal-digital-universe. It requires "multiliteracies", all in a constantly and rapidly evolving technological environment, which are not yet fundamentally integrated into the basic literacy skills entrenched in school learning. How can creative writing instructors in higher education best prepare their students for the real-world contexts of their creative practice? One approach is to integrate the creative writing workshop with a focus on digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…A more recent research project demonstrated the value of IF as a springboard for creative writing (Lee, 2019). The teaching of digital fiction writing is also making its way into courses on creative writing and game design at the university level (see for example, Skains, 2019). However, research on the affordances of creating IF in interdisciplinary writing projects for L2 learning is largely unexplored territory.…”
Section: Maker Culture and Its Relevance For Multilingual Digital Sto...mentioning
confidence: 99%
“…A more recent research project demonstrated the value of IF as a springboard for creative writing (Lee, 2019). The teaching of digital fiction writing is also making its way into courses on creative writing and game design at the university level (see for example, Skains, 2019). However, research on the affordances of creating IF in interdisciplinary writing projects for L2 learning is largely unexplored territory.…”
Section: Maker Culture and Its Relevance For Multilingual Digital Sto...mentioning
confidence: 99%
“…We decided that the climate change education curricula we wrote would be supported with a quantitative psychology‐based measure of attitude change. The curricula would also incorporate an interactive digital narrative, [19] to convey climate change in a novel manner. Emboldened by my time at Welsh Crucible, and so that I would have time to work on the climate change education, I asked my employer to change my contract to incorporate science communication, thereby shifting my focus from 100 % lab‐based research to 50:50 lab‐based : science communication‐based research.…”
Section: Steaming On Ahead: Developing Targeted Outreach Programmes Amentioning
confidence: 99%
“…Workshop 2 was centred around readinga ni nteractive digital narrative (IDN), [19] No World 4T omorrow, [23] writtenb ym y colleagueD r. Lyle Skains. This addressed both individual behaviours and political-economic systemic changes.…”
Section: Youa Nd Co 2 In Practice:w Hat Worked and What Didn't Work?mentioning
confidence: 99%
“…The workshops encompass an innovative combination of interactive chemistry lessons, reading, and discussion of interactive digital narratives (IDNs) for themes of climate change and personal choice, and student construction of their own IDNs on themes of climate change and personal responsibility. This learning intervention is a multiliteracies approach (Cope and Kalantzis 2009;Skains 2019b) to teach the science of climate change through digital literacy, interactivity, creative writing, game design, discussion, and group and individual work. Multiliteracies is a design-based pedagogical approach that develops multiple professional, developmental, and cognitive skills through the holistic layering of multiple practical activities within any given course or lesson.…”
Section: Introductionmentioning
confidence: 99%